Positive species diversity and above‐ground biomass relationships are ubiquitous across forest strata despite interference from overstorey trees. (7th July 2016) - Zhang, Yu; Chen, Han Y. H.; Taylor, Anthony R.
Summary: There is growing concern over rates of global species diversity loss and its implications on healthy ecosystem functioning. While positive relationships between tree species diversity and forest biomass production have been observed, forests are structurally complex, consisting of understorey vegetation layers that also contribute to ecosystem functioning as they often account for the majority of species richness. However, relationships between understorey vegetation diversity and function are largely unexplored. Further, few studies have simultaneously assessed how both overstorey and understory vegetation interact and contribute to overall ecosystem function. By analysing Canada's National Forest Inventory data base using structural equation modelling, we explored the relationships between species richness and above‐ground biomass production across forest vegetation strata while accounting for potentially confounding factors, including climate, physical site characteristics and forest ageing. We found positive relationships between species richness and biomass production across all forest vegetation layers, but the relationship was strongest for the overstorey layer. Species richness of the understorey tree, shrub and herb layers was positively related to overstorey species richness. However, overstorey biomass had a negative effect on the biomass production of all understorey layers. Our results suggest that resource filtering by overstorey trees might have reduced the strength of the positive diversity–productivity relationships in the forest understorey, supporting previous hypotheses that the magnitude and direction of diversity–productivity relationships is context specific and dependent on the conditions of the surrounding environment. Further, heterogeneity in understory resources, as affected by the overstorey, may promote niche complementarity as the main mechanism driving diversity–productivity relationships in understorey vegetation. Abstract : Lay Summary